Study of the Theory of Actual Division in Turkology - Dzhumamuratov K. A. (Researchparks Publishing, 2022)
This article talks about the syntactic expressions of the theme of Rhema, in comparison of the German and Karakalpak languages, common and universal, and specific of these languages.